Effect of Electrode Moisture in DC Current SMAW Process on The Welding Results of Low Carbon Steel - Hafni Hafni; Novriwan Novriwan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2023)
Welding using a wetelectrode and polarity selection is thought to affect the defects that usually arise in the welding results of low carbon steel type ST 37. To find out how much influence the humidity of the electrode and polarity have on defects in low carbon steel welding results, a study was carried out using oil fluids as a moisturizing agent for the electrode. The process of humidifying the electrode is carried out by immersing the electrode until it absorbs the oil fluid before welding it on the base metal. After welding with these electrodes, a metallographic test was carried out to observe the macrostructure and microstructure of the welding results. The conclusion that can be drawn from the test results is that the humidity of the electrode by oil does not affect the defects that arise in low carbon steel welding results as long as it does not damage the flux from the electrode.